Expectancy of success, attainment value, engagement, and Achievement: A moderated mediation analysis. (April 2019) - Putwain, David W.; Nicholson, Laura J.; Pekrun, Reinhard; Becker, Sandra; Symes, Wendy
Abstract: The aim of this study was to examine how expectancy of success, attainment value, and their interaction predicted behavioural engagement, and how behavioural engagement, in turn, predicted achievement. Data were collected from 586 English students aged 10–11 years in their final year of primary school. Expectancy of success was positively related to subsequent achievement directly and indirectly, mediated by behavioural engagement, over and above the variance accounted for by prior achievement and behavioural engagement. Indirect relations from expectancy of success to achievement were moderated by attainment value. Higher attainment value protected performance from low expectancy of success by increasing behavioural engagement. The compensatory role of high attainment value diminished at higher levels of expectancy of success. Highlights: Expectancy was directly linked to achievement. Expectancy was also indirectly linked to achievement, mediated by engagement. Indirect relations were moderated by achievement value. At high achievement value, the indirect relation was weaker. At low achievement value, the indirect relation was stronger.